Polymorphisms of the DNA repair gene EXO1 modulate cognitive aging in old adults in a Taiwanese population - Lin, Eugene; Kuo, Po-Hsiu; Liu, Yu-Li; Yang, Albert C.; Tsai, Shih-Jen (DNA repair, 2019)
•The EXO1 rs1776181, rs1776177, rs1635510, and rs2526698 SNPs are associated with cognitive aging.•Interactions between the EXO1 gene and physical activity influence cognitive aging.•Interactions between the DCLRE1C gene and physical activity influence cognitive aging.•Interactions between the EXO1 and RAD51C genes contribute to cognitive aging. Evidence indicates that the age-related neuropathological mechanisms associated with DNA repair genes may contribute to cognitive aging and Alzheimer’s disease. In this study, we hypothesize that single nucleotide polymorphisms (SNPs) within 155 DNA repair genes may be linked to cognitive aging independently and/or through complex interactions in an older Taiwanese population. A total of 3,730 Taiwanese subjects aged over 60 years from the Taiwan Biobank were analyzed. Mini-Mental State Examination (MMSE) was administered to all subjects, and MMSE scores were used to measure cognitive functions. Our data showed that out of 1,652 SNPs, the rs1776181 (P = 1.47 × 10−5), rs1776177 (P = 8.42 × 10-7), rs1635510 (P = 7.97 × 10-6), and rs2526698 (P = 7.06 × 10-6) SNPs in the EXO1 gene were associated with cognitive aging. The association with these SNP remained significant after performing Bonferroni correction. Additionally, we found that interactions between the EXO1 and RAD51C genes influenced cognitive aging (P = 0.002). Finally, we pinpointed the influence of interactions between EXO1 and physical activity (P < 0.001) as well as between DCLRE1C and physical activity (P < 0.001). Our study indicated that DNA repair genes may contribute to susceptibility in cognitive aging independently as well as through gene-gene and gene-physical interactions.